2007
DOI: 10.1007/s00192-006-0254-z
|View full text |Cite
|
Sign up to set email alerts
|

Translabial ultrasound assessment of the anal sphincter complex: normal measurements of the internal and external anal sphincters at the proximal, mid-, and distal levels

Abstract: The purpose of this study was to measure the internal and external anal sphincters using translabial ultrasound (TLU) at the proximal, mid, and distal levels of the anal sphincter complex. The human review committee approval was obtained and all women gave written informed consent. Sixty women presenting for gynecologic ultrasound for symptoms other than pelvic organ prolapse or urinary or anal incontinence underwent TLU. Thirty-six (60%) were asymptomatic and intact, 13 symptomatic and intact, and 11 disrupte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
1
23
1
1
Order By: Relevance
“…In particular, no significant differences were found between the two methods with respect to the thickness of both the internal and the external anal sphincter; indeed, our results were similar to those reported in the literature for AES [9][10][11][12], and comparable to those obtained with magnetic resonance imaging [13,14] The use of the disposable anoscope allows optimal positioning of the echographic transducer reducing patient discomfort (through elimination of the to-and-fro movements within the anal canal), and better acoustic coupling, and eliminates the use of a condom or balloon which can expand asymmetrically and alter the plane of imaging. The use of the disposable anoscope adds only about 4 Euros to the cost, but has the advantage that it prevents the endoscope coming into contact with the patient, thereby reducing the likelihood of transmission of infective agents.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, no significant differences were found between the two methods with respect to the thickness of both the internal and the external anal sphincter; indeed, our results were similar to those reported in the literature for AES [9][10][11][12], and comparable to those obtained with magnetic resonance imaging [13,14] The use of the disposable anoscope allows optimal positioning of the echographic transducer reducing patient discomfort (through elimination of the to-and-fro movements within the anal canal), and better acoustic coupling, and eliminates the use of a condom or balloon which can expand asymmetrically and alter the plane of imaging. The use of the disposable anoscope adds only about 4 Euros to the cost, but has the advantage that it prevents the endoscope coming into contact with the patient, thereby reducing the likelihood of transmission of infective agents.…”
Section: Discussionsupporting
confidence: 92%
“…Most studies do not describe any anal sphincter levels 5,8e10,14,17,25 or when they do report on imaging different transverse planes, they do not include the subcutaneous level. 6,12,13,15 Peschers et al 16 report visualizing the anal canal from the puborectalis to the subcutaneous EAS, but provided no data on images at each level. Only one previous study using TPU has described visualization of the three levels of the EAS including the subcutaneous level 18 and was able to obtain images of all three levels for all 20 nulliparous as well as all 20 primiparous participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, difficulty in interpreting EVU images has been reported in up to 24% of women. 8,9 Further studies have been able to describe both normal anatomy as well as anal sphincter disruptions with EVU using a vaginally inserted side-fire transrectal probe, 10,11 a linear "small parts" transducer, 14 and a standard, vaginal probe, 6,12,13,15 the latter two of which were placed at the vaginal introitus. Frudinger et al 7 used a 10 MHz rectal endoprobe and a 10 MHz modified vaginal probe and found that the sensitivity and specificity of EVU for the detection of IAS defects was 44 and 96% and for EAS defects was 48 and 88%, respectively, taking EAU as the reference standard.…”
Section: Introductionmentioning
confidence: 99%
“…This aside, the coloproctological fraternity is indebted to his far-reaching predictive concepts [149]. Future anatomical analysis in disease states should follow his lead to define assessment parameters that are clinically important [4,150]. These future studies should try to define the complexity of inter-related reflexes which he described in order to ascertain their functional significance in both health and disease.…”
Section: Discussionmentioning
confidence: 92%
“…The early cadaveric anatomical studies of the anal sphincters and the pelvic floor conducted by Professor Ahmed Shafik have remained controversial following refinements in our understanding of the disposition of the sphincter musculature with the advent of modalities providing multiplanar and reconstructed axial images [1][2][3][4]. This work focusing in particular on the structure of the external anal sphincter (EAS) as a triple interconnected system of U-shaped loops which sequentially compresses opposing anal segments [5] proposes a mechanism of single-loop continence from any of these parts following partial EAS division during fistulectomy [6,7].…”
Section: Introductionmentioning
confidence: 99%